TANTANGAN DAN SOLUSI DALAM PENDIDIKAN KESEHATAN MENTAL DI SEKOLAH - Rizka Adela Fatsena; Entin Solihah (Jurnal Kesehatan, 2025)
Mental health education in schools is becoming increasingly important due to the growing awareness of the impact of mental health on students' well-being and academic achievement. However, its implementation faces various challenges. The research method in this review uses literature. The results showed that to face these challenges, a holistic approach is important in addressing mental health challenges in schools. This means involving various parties (school, family, health professionals) and integrating mental health into various aspects of school life. Therefore, this study suggests the implementation of a multi-dimensional strategy, which means combining various solutions to create a comprehensive approach in improving the eflectiveness of mental health education in schools.